Investigation of Geofiltration Properties of Clay Soils - Klizas, Petras; Gadeikis, Saulius; Norkus, Arnoldas; Žilionienė, Daiva; Dundulis, Kastytis (The Baltic Journal of Road and Bridge Engineering, 2014)
Filtration properties of clay (Kuksa mine, Lithuania) were investigated and analysis of the results was done. Investigations were carried out using a permeameter with a varying hydraulic head. A potential dependence of the clay hydraulic conductivity values on the filtration process duration as well as hydraulic gradient and compaction range were determined. The importance of the clay structural peculiarities, carrying out filtrations through clay paste, natural structure and compacted samples was evaluated. It was determined that the clay hydraulic conductivity values varied greatly only at the beginning of the filtration while, later on, when continuing the filtration for a few days, the change reduced. This shows that, during the filtration, there are structural clay-forming unit rearrangements that are taking place. The filtration investigation of the clay paste studies show that there exist clay structural links different changes the filtration capacity of clay. The determined varying behaviour of the clay and the clay paste in the course of filtration as well as under various loads must be evaluated in the design and reconstruction of roads with subgrade of the clayey soils.